IMPLEMENTASI DAN PENGUJIAN KINERJA ORACLE 10g REAL APLICATION CLUSTER (RAC) PADA SISTEM OPERASI SUN SOLARIS 10 - Santoso, Gatot Budi; Wirawan, Yanuar Indra (PETIR, 2015)
During the implementation of database system, needs of getting fast, accurate and high-availability data, has become major clauses for the implementation of “high-availability” system. Oracle 10g RAC is a clustered database solution that requires a two or more node hardware configuration capable of working together under a clustered operating system. A clustered hardware solution is managed by cluster management software, usually provided by the hardware vendor. The operating system is also responsible for providing access to the shared disk subsystems. Parameters that used for the performance testing and analyzing of Oracle 10g Real Application Cluster are the cpu idle, free memory, SGA, buffer cache, and shared pool. As result for the performance testing and analyzing, it can be concluded that Oracle 10g Real Application Cluster was really good for the implementation of “high-availability system” concept. But it all depends to the analysis for its system.